Positive Findings of Blood Cultures in Febrile Children Presenting with Thalassemia Major in a Tertiary Care Hospital - Fatima, Itrat; Affan, Wafia; Hameed, Hira; Amber, Wajeeha; Saeed, Sumbal; Khan, Imran Mahmood (Journal of Rawalpindi Medical College, 2023)
Objective: To assess status of bacterial pathogens in thalassemia major patients presenting with fever in a tertiary care hospital Methods: A retrospective descriptive study was conducted at –removed for blind review---from November, 2020 to October, 2021 in which 102 patients of thalassemia major who presented with fever and were suspicious of having septicemia were enrolled. Their demographic characteristics and pathological findings were noted in this study. Standardized approach was followed for blood withdrawal and sample collection required for performing blood cultures. The data was analyzed with SPSS version 21. Results: Females were in majority. Total 57 (56.0%) of patients had positive blood culture. The most frequent bacterial pathogen was Klebsiella pneumonia 13 (12.7%), followed by E-coli 11 (10.7%), staphylococcus aureus 7 (6.8%), pseudomonas 8 (7.8%) and streptococcus type pathogens 6 (5.8%). Conclusion: Positive culture findings were high in the thalassemia major patients who presented with fever.